THE COMPLEXITY OF SENTENCE STRUCTURES IN READING TEXTS OF ENGLISH TEXTBOOKS USED FOR THE FIRST GRADE IN SENIOR HIGH SCHOOL - Laeli Nur Ramdhani; I Made Sujana; Lalu Thohir; Agus Saputra (Journal of English Education Forum (JEEF), 2021)
This study aims to find out the complexity of sentence structure in the reading text of Grade X textbooks provided by several publishers. This research his descriptive qualitative with the support of some descriptive quantification. The source of data taken from reading texts used by senior high school students grade X published by Cultural and Educational Ministry of Indonesia, Yrama Widya, and PT. Tiga Serangkai Pustaka Mandiri. The data of this research are all sentences found in the reading texts e.g., descriptive text, recount text, and narrative text. The data of this research deal with complexity of sentence structure measured by the number of simple sentences, compound sentence, complex sentence, and compound complex sentence. The result of this study shows that each textbook contains different percentage of simple sentences, compound sentences, complex sentences, and sentences. The textbooks published by Kementrian Pendidikan dan Kebudayaan and Yrama Widia has the highest percentage of complex sentence (51.5%;37.9%, respectively). In contrast, the highest percentage in Tiga Serangkai Mandiri is simple sentence (55.7). The least percentage is compound sentence which can be seen in Kementrian Pendidikan dan Kebudayaan and Yrama Widia (8.6%, 4.6%, respectively). The small percentage of compound complex is shown in the textbook published by Kementrian Pendidikan dan Kebudayaan and Tiga Serangkai Mandiri (5.7%, 9.0%, respectively).